Establishing risk-based recall interval for caries management among 11-12-year-old Pakistani children - Muhammad Taqi; Ishak Abdul Razak; Norintan Ab-Murat; Syed Jaffar Abbas Zaidi (BMC, 2022)
Abstract Background This study aims to investigate the rate of caries increment among 11-12-year-old Pakistani children over 18 months using modified International Caries Detection and Assessment Systems II (ICDAS) and subsequently establish an appropriate dental recall interval for our targeted population according to their caries risk intensity. Methods A prospective longitudinal study was conducted in Bhakkar, Punjab, Pakistan. The 226 children from seven schools of Bhakkar with the highest student enrolment were conveniently selected. Caries risk assessment was performed using a computer-based reduced Cariogram program. Caries increment among cavitated lesions was measured by modified Beck's method or adjusted caries increment. Two ICDAS II cutoffs were created for the analysis of cavitated lesion (ICDAS code 3-6) and cavitated plus non-cavitated lesion (ICDAS code A-6). Results At the risk assessment stage, 39.8% of the children were classified as low risk, 30.5% as medium risk, and 29.7% as high risk. Caries increment at both cutoff points increased with caries risk at all follow-ups. The highest caries increment was recorded at the third follow-up among high-risk children at cutoff 3-6 (1.95 ± 3.18) and A-6 (4.01 ± 4.31). However, the lowest caries increment was recorded at the third follow-up among low-risk children at cutoff 3-6 (0.18 ± 1.42) and A-6 (1.11 ± 3.33). Conclusion Based on the study findings for Pakistani children with cavitated lesions, the recommended risk-based recall interval for caries management is 18 months for those with low and medium caries risk and six months for those with high caries risk. On the other hand, recommendations for risk-based recall intervals for caries management in non-cavitated and cavitated lesions are six months for low-risk, moderate risk and high-risk for Pakistani 11-12-year-old children.